Natural history of Camponotus renggeri and Camponotus rufipes (Hymenoptera: Formicidae) in an Atlantic Forest reserve, Brazil - Pereira-Romeiro, M. P. [UNESP]; Vanin, G. T. [UNESP]; Azevedo-Silva, M.; Mori, G. M. [UNESP] (Springer Nature, 2022)
Widespread species face a wide variety of environmental challenges and their morphology, behavior, and natural history may change across their range. However, not rarely, natural history research is restricted to one or few locations. That is the case for Camponotus renggeri and C. rufipes. Both species occur across South America in different ecosystems, but most research on these species is restricted to the Brazilian savanna, known as Cerrado. Here, we describe the foraging area, nesting habits, and activity schedule of C. renggeri and C. rufipes in an Atlantic Forest reserve in SE Brazil. Inferred intraspecific foraging areas of nearby nests overlapped, especially for C. renggeri foraged exclusively during nighttime and C. rufipes remained active throughout the day, but with little intensity during daylight hours. Most nests of both species were composed of dry straw, and average foraging areas were 0.91 m2 for C. renggeri and 1.79 m2 for C. rufipes. C. renggeri. Our findings reinforce the importance of natural history and add to our knowledge on the ecology and behavior of C. renggeri and C. rufipes in Atlantic Forest.
Keywords: Daily activity; Foraging area; Hymenoptera; Neotropics; Nesting architecture; Sympatric species